Adaptation Test of Rice Varieties (Oryza sativa L. Var. Inpari) With Various Doses of NPK Fertilizer in Rice Field - Setiyawan, Andre; Octavia, Sri Devi; Maryati, Yekti; Widata, Sri; Pamungkas, Djoko Heru; Khairi , Alfassabiq (TERRA : Journal of Land Restoration, 2024)
Food crop commodities play an important role in meeting food needs in Indonesia, along with the increasing population. In addition, crop yields also play an important role in spurring economic growth, as a source of foreign exchange, and a source of life for most of Indonesia's population. Rice productivity in rice field areas is currently still decreasing, therefore appropriate technology is needed to increase productivity. One of the efforts made is by using superior varieties (Inpari) that are in accordance with agro-ecosystem conditions or specific locations. This study was conducted with the aim of determining the effect of growth and yield of rice varieties on various doses of NPK fertilizer in rice field. This research was conducted in Sentono Village, Kalasan District, Sleman Regency, Special Region of Yogyakarta Province, Indonesia in March–July 2019. The experimental design used was Split Plot with NPK fertilizer doses (200 and 300 kg ha−1) as the main plot and rice varieties (Inpari 6, Inpari 30, Inpari 32, Inpari 43, and Inpari 33) as subplots, and with 3 replications. The results showed no interaction between fertilizer doses and rice varieties. Inpari 42 with NPK fertilizer 300 kg ha−1 increased plant height, number of tillers productive, panicle length, number of filled grain/panicle, grain weight/clump, and production of dry grain. The highest production of dry grain was Inpari 42 (6.56 ton ha−1), while the lowest production of dry grain was Inpari 30 with NPK fertilizer 200 kg ha−1 (4.35 ton ha−1). These findings highlight the potential of specific variety-fertilizer combinations to optimize rice productivity and provide valuable insights for sustainable rice cultivation in Indonesia.